Effect of granular inclusions on the consolidation rate of dredged marine clay - S.M Johan, Siti Farhanah; Chan, Chee-Ming (Penerbit Uthm, 2018)
This study investigates the granular inclusion such as sand, palm oil clinker and recycled pavement materials, in conjunction with dredged marine clay from dredging project at Kuala Perlis, Malaysia to improve the consolidation rate. Dredged marine clay (DMC) known as geo-waste because of poor engineering properties. Thus, dredged and dump methods become an option to certain countries without any treatment before dumping it back to open waters. In addition, this method clearly gives the negative potential towards the environment especially the contamination of DMC to the marine ecosystems. Therefore, this study investigated the effect of granular inclusion to accelerated consolidation time and determine whether it can be reuse or not by used the 1D oedometer test. The results showed that the use of granular materials does suggest the increasing of consolidation rate as well as strengthen the soil particles of DMC. Moreover, the effective use of waste granular materials such as palm oil clinker and recycled pavement materials contributes to developing a sustainable society by reducing the huge quantities of solid wastes and establishing a sound environment. Keywords: Dredging; Dredged clay; Granular materials; Oedometer; Consolidation rate